ROLE OF INFORMATION TECHNOLOGY IN EDUCATION IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Anvar Rashidovich Meliboyev; Zarnigor Bektemirova (Galaxy International Interdisciplinary Research Journal, 2022)
Preschool educational organizations need to introduce advanced pedagogical and information technologies into the educational process and improve the efficiency of the educational process.